Patent Laws in India and its Impact on Pharmaceutical Industry - S.B. PURANIK; MAMATA SANGAMESH; MONA GOLSHAN.S (International Journal of Pharma and Bio Sciences, 2010)
Patent is an intellectual property right relating to inventions and is a grant of exclusive right, for limited period, provided by the Government to the patentee, in exchange of full disclosure of this invention, for excluding others, from making, using, selling, importing the patented product or process producing that product for those purposes. The purpose of this system is to encourage inventions by promoting their protection and utilization so as to contribute to the development of industries, which in-turn contribute to the promotion of technological innovation and to the transfer and dissemination of technology. Under the system, Patents ensure property rights for the invention for which patent have been granted, which may extremely valuable to an individual or a Company. Patent right is territorial in nature and a patent obtained in one country is not enforceable to other country. The inventors/ assignees are required to file separate patent applications in different countries for obtaining patent in those countries.